Review of High Level Endodontic Research in PubMed Index Journals from Iran - Eghbal, Mohammad Jafar; Torabzadeh, Hassan (Iranian Endodontic Journal, 2012)
Introduction: This study aimed to evaluate patents as well as high level researches including systematic reviews/meta-analyses and randomized controlled clinical trials (RCT) published in scientific journals by Iranians endodontic. Materials and Methods: The study started with targeted searches of PubMed as well as World Intellectual Property Organization and United State Patent and Trademark Office. Results: There were 4 filed/granted patents, 2 systematic reviews/meta-analyses and 25 RCTs. Patents were related to endodontic/dental (bio)materials. Performing a topic sorting, 15 RCTs were about vital pulp therapy and 8 about anesthesia and pain. More than 55% of these articles originated from three University of Medical Sciences: Shahid Beheshti (22.2%), Kerman (18.5%) and Mashad (14.8%). Conclusion: Vital pulp therapy was the most important topic amongst endodontic high level evidence articles.